Uji Sifat Listrik Film Tipis LiTao3 dan LiTaFe2O3 - Indro, M. N.; Sastri, B.; Nady, L.; Ridwan, E.; Syafutra, H.; Irzaman, Irzaman; Siswadi, Siswadi (BERKALA FISIKA, 2010)
Lithium Tantalat (LiTaO3) pure and LF Thin films has been done is cube-shaped Ferium Oxide Fe2O3 (LFT) with a cube-shaped variation 0%, 2.5%, 5% and 7.5% above the substrate Si (100) p-type using a chemical solution deposition (CSD) method by spin coating technique at 3000 rpm rotational speed for 30 seconds. LF Thin films made with 1 M concentration and annealing at a temperature of 850 ° C for Si substrates. Thin films on p-type silicon substrates were characterized thickness using volumetric method, characterization conductance by using LCR meter, test the current-voltage characterization (IV curve) using Keithley Meter IV model 2400, characterization of dielectric constants and time constants using the oscilloscope and function generator and pyroelectric characterization using Wetsteind bridge circuit which in furnace (combustion) to a temperature of 1300C by calculating the increase in temperature variation. From the characterization results indicate thickness thickness increases with the number pendadah ferium given oxide. IV characterization results showed that LF and LFT thin film is a dielectric resistor.Hasil are contained in a thin film on p-type silicon substrate varies in accordance with the addition pendadah used were 0%, 2.5%, 5% and 7.5%. Keywords: LF, LFT, thin film, CSD, spin coating, annealing, cube-shaped, thickness, dielectric constant, time constant-voltage current, ferium oxides, pyroelectric.